2009
DOI: 10.4049/jimmunol.182.2.1167
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Deficiency Reduces the Severity of Experimental Autoimmune Encephalomyelitis

Abstract: Galectin-3 (Gal-3) is a member of the beta-galactoside-binding lectin family and plays an important role in inflammation. However, the precise role of Gal-3 in autoimmune diseases remains obscure. We have investigated the functional role of Gal-3 in experimental autoimmune encephalomyelitis (EAE) following immunization with myelin oligodendrocyte glycoprotein (MOG)35-55 peptide. Gal-3 deficient (Gal-3-/-) mice developed significantly milder EAE and markedly reduced leukocyte infiltration in the CNS compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 46 publications
4
137
0
1
Order By: Relevance
“…73 Gal-3 has a known role in atopic dermatitis and asthma by promoting an anti-inflammatory Th2 response, while it diminishes the Th2 response in Paracoccidioides infection by negatively regulating IL-10 production. 74 Gal-3 affects Th1, 75 Th2, 74 and Th17 responses, 76 depending on the infecting pathogen. Presumably, this is dependent on the type of receptors involved and their interaction with the stimulant.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…73 Gal-3 has a known role in atopic dermatitis and asthma by promoting an anti-inflammatory Th2 response, while it diminishes the Th2 response in Paracoccidioides infection by negatively regulating IL-10 production. 74 Gal-3 affects Th1, 75 Th2, 74 and Th17 responses, 76 depending on the infecting pathogen. Presumably, this is dependent on the type of receptors involved and their interaction with the stimulant.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…Interestingly, gal3 also suppresses the regulatory T cell response through downregulating IL-10 release by DCs and, thus, induces Th1/Th17 responses to aggravate experimental autoimmune encephalomyelitis (EAE) (11). Gal3 2/2 mice were demonstrated to have reduced inflammation and neutrophil recruitment in infections by Streptococcus pneumoniae and T. gondii (6), atherosclerosis (12), EAE (11), and dextran sulfate sodium-induced colitis (13). However, little is known about the relationship between gal3 and production of IL-23/IL-17A-axis cytokines.…”
mentioning
confidence: 99%
“…Some evidence suggested that Galectin-3 is associated with a decrease in regulatory T (Treg) cell frequency and thus influences the course of experimental autoimmune encephalomyelitis and Leishmania major infection (98,99). These results raise the question of whether Galectin-3 deficiency also impaired the number of Treg cells in an experimental model of B16-F1 murine melanoma.…”
Section: It Is Well Established That Nk Cells and Cd8mentioning
confidence: 62%